2020
DOI: 10.3390/nano10050966
|View full text |Cite
|
Sign up to set email alerts
|

CMOS-Compatible and Low-Cost Thin Film MACE Approach for Light-Emitting Si NWs Fabrication

Abstract: Silicon nanowires (Si NWs) are emerging as an innovative building block in several fields, such as microelectronics, energetics, photonics, and sensing. The interest in Si NWs is related to the high surface to volume ratio and the simpler coupling with the industrial flat architecture. In particular, Si NWs emerge as a very promising material to couple the light to silicon. However, with the standard synthesis methods, the realization of quantum-confined Si NWs is very complex and often requires expensive equi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 48 publications
1
17
0
Order By: Relevance
“…The emission of all the samples is reported in Figure 8g, demonstrating their quantum confinement nature. In fact, the PL is redshifted by increasing the average diameter of the Si NWs, in perfect agreement with quantum confinement theory [72,135].…”
Section: Metal Film or Two Step Macesupporting
confidence: 87%
See 2 more Smart Citations
“…The emission of all the samples is reported in Figure 8g, demonstrating their quantum confinement nature. In fact, the PL is redshifted by increasing the average diameter of the Si NWs, in perfect agreement with quantum confinement theory [72,135].…”
Section: Metal Film or Two Step Macesupporting
confidence: 87%
“…It is worth to note that H 2 O 2 injects holes into the Si valence band independently of the doping type and level. What changes between different doping type and level is the etching rate of the process [ 72 ]. A MACE process may result in the synthesis of porous Si with different pores dimension or in the fabrication of Si NWs.…”
Section: State Of Art Of Si Nw Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…For both samples, any residual metal impurities are expected to remain close to the tips of the nanowires, therefore, affecting less than 0.2% of the DBs that we probe experimentally. The metal contamination in SiNWs produced by MACE, in contrast with those produced by the vaporliquid-solid method with a metal catalyst, has been found negligible by different experimental methods [21][22][23][24]. The full process led to a dense carpet of straight silicon nanowires, fully passivated with H and with structural parameters dependent on the process details ( Fig.…”
Section: Methodsmentioning
confidence: 96%
“…Indeed, as far as the authors know, no case of gas sensing devices based on Si NW light emission are reported in the literature. Recently, our group demonstrates the use of a modified Metal-Assisted Chemical Etching (MACE) process, by using ultra-thin gold (Au) films to synthesize RT light-emitting Si NWs [ 56 ] due to the quantum confinement effect, as already investigated in our works [ 57 , 58 , 59 , 60 , 61 , 62 ]. This approach is industrially compatible, maskless, and cost-effective.…”
Section: Introductionmentioning
confidence: 99%